Self-Care of Chronic Illness Inventory: Scoping Review - Sri Rejeki Anugerahni Martono Dianto; Meira Erawati; Fitria Handayani (GLOBAL HEALTH SCIENCE GROUP, 2025)
The increasing prevalence of chronic diseases and the complexity of comorbidities demand a systematic management approach. The Self-Care of Chronic Illness Inventory (SC-CII) is an instrument that assesses self-care behaviors through three main domains: maintenance, monitoring, and management. This study aims to conduct a scoping review of the validity, reliability, and application of the SC-CII across chronic conditions and cultural settings. The method follows the PRISMA-ScR guidelines with an article search through PubMed and Scopus databases with articles from 2022 through 2024. Of the 765 articles identified, five were used that met the criteria. Articles that did not meet the inclusion criteria were eliminated, including publications over five years old, not available in open access, not in English, and not scientific articles. Studies were also eliminated if they had incomplete data, duplication, could not be downloaded in full, did not have an abstract, or did not match the focus of the study. Articles discussing chronic stroke and articles with irrelevant discussion were also excluded from the review. The results showed that the SC-CII has high construct validity and reliability in both the original and translated versions. The three domains showed a consistent and theoretically relevant factor structure. This instrument is used effectively in populations with multiple chronic conditions such as hypertension, diabetes, heart failure, COPD, and chronic kidney disease. The SC-CII can identify contextual determinants in self-care decision making and support the development of culturally adaptive educational interventions. In conclusion, the SC-CII is a valid and reliable multidimensional instrument, and contributes significantly to evidence-based nursing practice and the person-centered care approach.